The effect of lemongrass (Cymbopogon citratus) supplement on growth performance and carcass characteristics of Pekin ducks - Linh, N. T.; Guntoro, B.; Qui, N. H.; Khang, N. D.; Dau, N. T.; Vui, N. V. (Diponegoro University, 2020)
Livestock including duck as one of crucial sector in agriculture, contributes a large proportion to Vietnam’s economic and to Mekong delta’s economic as well. Recently, herbal supplementation in feed is common which has brought many benefits for farmers and lemongrass is one of herbs is commonly used in many studies. A total of 96 ducks aged from 1 to 8-week-old was conducted through four treatments and three replicates per treatment. The experiment was a completely random design which aimed to estimate the effect of lemongrass powder on duck’s performance and carcass characteristics. The birds in the treatments were fed by the same feed but different supplement ratio of lemongrass powder (0; 0,5; 1; 1,5%). Besides, the birds were fed and watered ad libitum in all of the treatments. The conclusion showed that there was a linear decrease in feed intake, linear improvements in live weight gain and feed conversion as the proportion of lemongrass in the diet was increased from zero to 1.5%, inclusion of 1.5% lemongrass in feed will help the ducks increase their daily weight gain, improve feed intake and feed conversion ratio (P<0.05). However, lemongrass powder had no effect on carcass characteristics (P>0.05).